Return to IXIL: Maya society in an eighteenth-century Yucatec town - Christensen, Mark, author; Restall, Matthew, author; University Press of Colorado, publisher (Colorado State University. Libraries, 2019)
An examination of 100+ previously unstudied colonial-era Maya wills from the Yucatec town of Ixil. These testaments--some of the only surviving documentation of colonial inhabitation--offer unprecedented depictions of material and spiritual life from 1738 to 1779 and are rare and rich resources of Maya language.--Provided by publisher.
Notaries and the making of testaments in Ixil -- Defending and governing Ixil -- Ixil's economic life -- God in Ixil -- Family in Ixil.
Keywords: Wills -- Mexico -- Yucatán (State); Indians of Mexico -- Mexico -- Yucatán (State) -- Social conditions -- 18th century -- Sources; Indians of Mexico -- Mexico -- Yucatán (State) -- History -- 18th century -- Sources; Mayas -- Social conditions -- 18th century -- Sources; Mayas -- History -- 18th century -- Sources; Ixil (Mexico) -- Social life and customs; Ixil (Mexico) -- History